Screening of local, improved and hybrid rice genotypes against leaf blast disease (Pyricularia oryzae) at Banke district, Nepal - Acharya, Basistha; Shrestha, Sunder Man; Manandhar, Hira Kaji; Chaudhary, Bedanand (Journal of Agriculture and Natural Resources, 2019)
Rice (Oryza sativa) is the major cereal crop of Nepal which is being faced by the devastating rice blast disease caused by Pyricularia oryzae Cavara. An experiment was conducted to screen rice genotypes against leaf blast disease under disease conducive upland nursery at Regional Agricultural Research Station (RARS), Khajura, Banke, Nepal during July to November, 2016. A total of 101 rice genotypes (comprising of local, improved and hybrid) including resistant and susceptible check were screened in a randomized complete block design with two replications. Disease scoring was done beginning from the 20th days of sowing by using the disease rating scale 0-9. Amongst the tested 101 rice genotypes, 28 genotypes were found resistant, 15 genotypes were moderately resistant, 16 genotypes were moderately susceptible, 39 genotypes were susceptible and 3 genotypes were highly susceptible to leaf blast. The information revealed from this study could be helpful for rice leaf blast disease management and utilizing these resistant and moderately resistant genotypes for further resistance breeding program.